Perencanaan Strategis Sistem Informasi Peternakan Domba Di Ps4 Wira Tani Karawang Dengan Metode Ward Dan Peppard - Sadam Alfian Pradana; Rizki Aji Mahardika; Evy Nurmiati (LPPM Universitas Al Asyariah Mandar, 2023)
This study aims to plan the information system strategy for sheep farming at P4S Wira Tani in Karawang, using the Ward and Peppard framework. The identified challenges include the underutilization of information technology in sheep farming activities, such as the lack of a stock feed recording system, ineffective sheep disease management, and inadequate data recording for malnourished or defective lambs. By applying Value Chain, SWOT, PEST, and McFarlan Strategic Grid analyses, this research aims to identify the information system needs of sheep farming at P4S Wira Tani and develop a portfolio of IT strategies. The strategic planning outcomes will provide guidance to improve work efficiency and gain a competitive edge in sheep farming activities. It is expected that this research will assist P4S Wira Tani in the development and sustainable implementation of an information system.